The Mexican state of Chiapas: What has changed in twenty years? - Ávila Romero, Agustín; Sulvarán López, José Luis; Ávila Romero, León Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This paper looks over the economic and social causes that allowed the zapatista rebellion 20 years ago, to show that this fact caused the increased arrival of economic resources to the State of Chiapas, and to expose, in turn, how the money by the Government of the State and the official municipalities were used. It is concluded that the public finances of Chiapas are extremely weak and that despite the increased capital infusion that it has received, the State is indebted and in similar conditions of marginalization and poverty of those of the two decades ago.